MENGEMBANGKAN SKILL MENGAJAR (TEACHING SKILL) MAHASISWA CALON GURU MENGGUNAKAN MULTY STRATEGIES - Lufri Lufri; Sudirman Sudirman; Silvi Rahmi (Ta'dib, 2012)
This study was aimed at improving the quality of learning process of Strategi Pembelajaran Biologi subject and in turn teachers with good pedagogic competence and teaching skill can be realized. Learning syntax that was carried out in this subject was: (1) course orientation and pretest administration, (2) learning process employing multi-strategy (concept approach, modeling and drilling method), (3) explanation and lesson plan design exercise, and peer teaching practices based on the lesson plan. The lesson plans were assessed by using IPKG-1 and teaching practices were assessed by IPKG-2, and (4) posttest was assessed IPKG-2 to figure out the improvement on the students teaching skill. The findings showed that there was significant improvement upon the students teaching skill in teaching practices by using multi-strategy.Kata kunci:   skill mengajar, mahasiswa calon guru, multy strategy